Reproductive Outcomes in Cases of Subclinical Hypothyroidism and Thyroid Autoimmunity: A Narrative Review - Bruno Ramalho de Carvalho; Andrea Prestes Nácul; Cristina Laguna Benetti-Pinto; Ana Carolina Japur de Sá Rosa-; José Maria Soares Júnior; Gustavo Arantes Rosa Maciel; Edmund Chada Baracat (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Thyroid diseases are relatively common in women in the reproductive period. It is currently understood that clinically-evident thyroid disorders may impair ovulation and, consequently, fertility. However, to date it has not been proven that high serum levels of thyroid-stimulating hormone and/or positivity for antithyroid antibodies are associated to a reduction in fertility, mainly in the absence of altered thyroxine levels. The present comprehensive review aims to present current data on the association between subclinical hypothyroidism and/or thyroid autoimmunity and reproductive outcomes.